Jumping off library shelves : a book of poems - Hopkins, Lee Bennett; Manning, Jane, 1960- (WordSong, an imprint of Highlights, 2015)
Here is the library, not just as a place that houses books, but as an experience. Fifteen poems celebrate the thrill of getting your first library card, the excitement of story hour, the fun of using the computer, the pride of reading to the dog, and the joy of discovering that the librarian understands you and knows exactly which books you'll love. The poems, compiled by noted poet and anthologist Lee Bennett Hopkins, pay homage to the marvels of books and reading. Accompanied by Jane Manning's colorful, imaginative illustrations, this collection lyrically celebrates the magic of libraries.